Hei-Gu-Teng Zhuifenghuoluo Granule Modulates IL-12 Signal Pathway to Inhibit the Inflammatory Response in Rheumatoid Arthritis. (29th May 2018) - Zheng, Kang; Chen, Zexu; Sun, Wen; Liu, Bin; Fan, Danping; Guo, Qingqing; Luo, Hui; Shen, Jiawen; Li, Li; He, Xiaojuan; Kou, Shuang; Li, Xiaoya; et al.
Abstract : Rheumatoid arthritis (RA) is a type of chronic systemic inflammatory disease; it has a very complicated pathogenesis, and multiple pathological changes are implicated. Traditional Chinese medicine (TCM) like Tripterygium wilfordii Hook. F. or Sinomenium acutum (Thunb.) Rehd et Wils. has been extensively used for centuries in the treatment of arthritic diseases and been reported effective for relieving the severity of RA. Hei-Gu-Teng Zhuifenghuoluo granule (HGT) which contains Periploca forrestii Schltr., Sinomenium acutum (Thunb.) Rehd et Wils., and Lysimachia paridiformis Franch . var. stenophylla Franch . was a representative natural rattan herb formula for the treatment of RA in China, but the mechanism has not been elucidated. This study aimed at exploring the mechanism of HGT on RA using the bioinformatics analysis with in vivo and in vitro experiment validation. The potential action mechanism was first investigated by bioinformatics analysis via Ingenuity Pathway Analysis (IPA) software. After that, we use experimental validation such as collagen-induced arthritis (CIA) mice model in vivo and U937 cell model in vitro. The bioinformatics results suggested that HGT may have anti-inflammatory characteristic on RA and IL-12 signaling pathway could be the potential key trigger. In vivo experiments demonstrated that HGT ameliorated the symptoms in CIA mice and decreased the production of inflammatory cytokines in both mice ankle joints and serum. Furthermore, HGT effectively inhibited the activation of IL-12R and STAT4 on IL-12 signaling pathway. In vitro experiments showed that HGT inhibited the production of IL-12R and STAT4 induced by IL-12 in lipopolysaccharide- (LPS-) stimulated U937 cells. Moreover, IL-12R knockdown was able to interfere with the inhibition effects of HGT on the production of these cytokines. Our results confirmed the anti-inflammatory property of HGT, which was attributed to its inhibition on IL-12 signaling pathway.